Charles Simms papers - Simms, Charles, 1755-1819.
Correspondence, Continental Army accounts and receipts, survey (1820) of lands in Randolph County, Va. (later W. Va.), and other papers. Correspondents include Joseph Kerr, George Mason, James Mercer, Charles H. Pelham, Cuthbert Powell, William D. Simms, and Samuel Tillett.
In part, photocopies.
Army officer, businessman, and public official.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Kerr, Joseph, -- 1765-1837 -- Correspondence; Mason, George, -- 1725-1792 -- Correspondence; Mercer, James, -- 1736-1793 -- Correspondence; Pelham, Charles H. -- Correspondence; Powell, Cuthbert, -- 1775-1849 -- Correspondence; Simms, William D. -- Correspondence; Tillett, Samuel -- Correspondence; United States. -- Continental Army; Surveying -- West Virginia -- Randolph County; United States -- History -- Revolution, 1775-1783.; Army officers; Businessmen; Public officials